2004
DOI: 10.1159/000077764
|View full text |Cite
|
Sign up to set email alerts
|

Systemic versus Topical Fluoride

Abstract: The actual mechanism of fluoride action is still a subject of debate. A dogma has existed for many decades, that fluoride has to be ingested and acts mainly pre-eruptively. However, recent studies concerning the systemic effect of fluoride supplementation concluded that the caries-preventive effect of fluoride is almost exclusively posteruptive. Moreover, epidemiologists have cast doubt on the validity of the ‘old’ studies dealing with fluoride use. The concept of the posteruptive fluoride effect is supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 28 publications
0
45
2
12
Order By: Relevance
“…Amelogenezis sırasında sistemik flor veya sürme sonrası maturasyonunu tamamlamamış mineye topikal flor uygulaması ile hidroksilapatit kristalindeki bütün hidroksil grupları yerine flor geçip florapatit [Ca 10 (PO 4 ) 6 F 2 ] oluşabilir. Ama doğada genellikle hidroksil gruplarının bazıları ile florun yer değiştirmesi ile florhidroksilapatit [Ca 10 (PO 4 ) 6 (F,OH) 2 ] oluşmaktadır.…”
Section: Florun Etki Mekanizmasıunclassified
See 2 more Smart Citations
“…Amelogenezis sırasında sistemik flor veya sürme sonrası maturasyonunu tamamlamamış mineye topikal flor uygulaması ile hidroksilapatit kristalindeki bütün hidroksil grupları yerine flor geçip florapatit [Ca 10 (PO 4 ) 6 F 2 ] oluşabilir. Ama doğada genellikle hidroksil gruplarının bazıları ile florun yer değiştirmesi ile florhidroksilapatit [Ca 10 (PO 4 ) 6 (F,OH) 2 ] oluşmaktadır.…”
Section: Florun Etki Mekanizmasıunclassified
“…Ama doğada genellikle hidroksil gruplarının bazıları ile florun yer değiştirmesi ile florhidroksilapatit [Ca 10 (PO 4 ) 6 (F,OH) 2 ] oluşmaktadır. Florapatit ve florhidroksilapatit oluşumu kristalin iç stresini düşürür ve kristalin asit ataklarında çözünme direncini arttırır.…”
Section: Florun Etki Mekanizmasıunclassified
See 1 more Smart Citation
“…There are some arguments, however, that the continuation of water fluoridation may be unnecessary especially in industrialized countries (Pizzo et al 2007) with regard to the following new evidences: 1. Anticaries effect of fluoride mostly exerts from its topical action rather than its pre-eruptive systemic absorption (Hellwig and Lennon 2004), 2. Experiences from some countries have shown that discontinuation of water fluoridation had no negative effect on caries prevalence of the population using that water (Seppa et al 2000, Kunzel et al 2000, 3.…”
Section: Effectiveness Of Caries Preventive Measuresmentioning
confidence: 99%
“…In addition to the multiple sources of fluoride, the systemic methods for delivering fluoride are also questioned because several studies have consistently indicated that fluoride's action relies mainly on its post-eruptive effect from topical contact with the tooth structure. The situation gets more obscure when the emerging problem of dental fluorosis can also be attributed to early uncontrolled ingestion of fluoride toothpaste by children as well as other sources (Hellwig & Lennon, 2004;Sampaio & Levy, 2011). This may give the impression that a widely used topical method of fluoride such as dentifrice is the solely contributor for dental fluorosis whereas a systemic method of fluoride such as water fluoridation is ineffective since it is a systemic method to deliver fluoride and most of fluoride effect comes from topical sources.…”
Section: Introductionmentioning
confidence: 99%